A versatile transfer printing technique through soap bubble - Qing Zhao; Kun Li; Feiyi Sun; Hechen Xu; Xiaoguang Hu; Jialiang Dong; Lixuan Che; Zhan Kang; Junshan Liu; Cunjing Lv; Ming Li (npj Flexible Electronics)
Abstract Stretchable and flexible electronics represent emerging and exciting directions for future electronics, while transfer printing plays an essential and mainstream role in integrating electronics onto application substrates. However, existing transfer printing approaches have restrictions for electronics in terms of stiffness and dimensionality, as well as limitations for substrates in terms of surface and adhesion. Here, we report a versatile soap bubble transfer printing technique that, through a volume modulation strategy, enables the adhesion-independent, damage-free, and low-contamination integration of rigid, flexible, and three-dimensional curved electronics onto substrates with complex surfaces and challenging adhesion. To demonstrate the versatility and compatibility of the soap bubble transfer printing technique, we performed not only special behaviors such as wrap-like, multilayer, selective, and interior printing, but also integrated flexible electronics onto various human organ models, which holds promise for health monitoring in both noninvasive and invasive manners.